Highly Resolved Papilionoid Legume Phylogeny Based on Plastid Phylogenomics - Choi, In-Su; Cardoso, Domingos; de Queiroz, Luciano P.; de Lima, Haroldo C.; Lee, Chaehee; Ruhlman, Tracey A.; Jansen, Robert K.; Wojciechowski, Martin F. (Frontiers in Plant Science, 2022)
Comprising 501 genera and around 14,000 species, Papilionoideae is not only the largest subfamily of Fabaceae (Leguminosae; legumes), but also one of the most extraordinarily diverse clades among angiosperms. Papilionoids are a major source of food and forage, are ecologically successful in all major biomes, and display dramatic variation in both floral architecture and plastid genome (plastome) structure. Plastid DNA-based phylogenetic analyses have greatly improved our understanding of relationships among the major groups of Papilionoideae, yet the backbone of the subfamily phylogeny remains unresolved. In this study, we sequenced and assembled 39 new plastomes that are covering key genera of evolution and morphological diversity in the subfamily. From 244 total taxa, we produced eight datasets for maximum likelihood (ML) analyses based on entire plastomes and/or concatenated sequences of 77 protein-coding sequences (CDS) and two datasets for multispecies coalescent (MSC) analyses based on individual gene trees. We additionally produced a combined nucleotide dataset comprising CDS plus matK gene sequences only, in which most papilionoid genera were sampled. An ML tree based on the entire plastome maximally supported all of the deep and most recent divergences of papilionoids (223 out of 236 nodes). The Swartzieae, ADA (Angylocalyceae, Dipterygeae, and Amburaneae), Cladrastis, Andira, and Exostyleae clades formed a grade to the remainder of the Papilionoideae, concordant with nine ML and two MSC trees. Phylogenetic relationships among the remaining five papilionoid lineages (Vataireoid, Dermatophyllum, Genistoid s.l., Dalbergioid s.l., and Baphieae + Non-Protein Amino Acid Accumulating or NPAAA clade) remained uncertain, because of insufficient support and/or conflicting relationships among trees. Our study fully resolved most of the deep nodes of Papilionoideae, however some relationships require further exploration. More genome-scale data and rigorous analyses are needed to disentangle phylogenetic relationships among the five remaining lineages.